Diagnostic value of serological and molecular biological tests for infectious mononucleosis by EBV in different age stages and course of the disease. Issue 6 (14th October 2020) - Shi, Ting; Huang, Linlin; Luo, Ling; Yu, Qiuyao; Tian, Jianmei
Abstract: Epstein‐Barr virus (EBV)‐based serologic antibody and viral nucleic acid assays have been found to be feasible means to diagnose infectious mononucleosis (IM) caused by EBV in children. In this study, we will further explore their diagnostic value for IM by EBV in different age stages and over the course of the disease. A collection of 616 children from clinically suspected IM cases was studied. Indirect immunofluorescence (IIF) for EBV‐specific antibody (Euroimmun) combined with plasma EB viral nucleic acid assay (real‐time fluorescence quantitative polymerase chain reaction reverse‐transcription polymerase chain reaction) were used as reference methods. The diagnostic efficiency of the peripheral blood routine test, serologic antibody test, and plasma EB viral nucleic acid assay for the diagnosis of IM was evaluated, respectively. The sensitivity, specificity, Youden' index and the area under curve (AUC) were 93.08%, 87.77%, 0.81 and 0.904 (95% confidence interval [CI]: 0.878–0.931) for the peripheral lymphocyte test (lymphocytosis > 5 × 10 9 /L), 98.27%, 91.13%, 0.89 and 0.947 (95% CI: 0.927–0.967) for the plasma EBV‐DNA test, and 84.08%, 96.33%, 0.80 and 0.902 (95% CI: 0.874–0.930) for the EBV viral capsid antigen (VCA)‐IgG avidity test. The plasma EBV‐DNA test has a higher diagnostic value than the VCA‐IgG avidity test in children aged <6 years, especially aged <3 years; the peripheral lymphocyte test and plasma EBV‐DNA test are suitable for the early stage of the disease, while the VCA‐IgG avidity test for after 7 days of the disease. EBV antibody detection (IIF) should be combined with EBV nucleic acid detection in children age <6 years and the early stage of the disease.